Loading of anthocyanins on chitosan nanoparticles influences anthocyanin degradation in gastrointestinal fluids and stability in a beverage. (15th April 2017) - He, Bo; Ge, Jiao; Yue, Pengxiang; Yue, XueYang; Fu, Ruiyan; Liang, Jin; Gao, Xueling
Highlights: Response surface-optimized preparation of anthocyanin-loaded chitosan nanoparticles. Box-Behnken design for high encapsulation efficiency and small particle size. First anthocyanin nanoparticles of carboxymethyl chitosan and chitosan hydrochloride. Chitosan nanoparticles delayed anthocyanin degradation in simulated GI fluid. Chitosan nanoparticles increased anthocyanin storage stability in a model beverage. Abstract: The optimal preparation parameters to create anthocyanin-loaded chitosan nanoparticles was predicted using response surface methodology (RSM). A Box-Behnken design was used to determine the preparation parameters that would achieve the preferred particle size and high encapsulation efficiency. The result suggested that the optimized conditions were 2.86 mg/mL carboxymethyl chitosan (CMC), 0.98 mg/mL chitosan hydrochloride (CHC) and 5.97 mg anthocyanins. Using the predicted amounts, the experimentally prepared particles averaged 219.53 nm with 63.15% encapsulation efficiency. The result was less than 5% different than the predicted result of 214.83 nm particle size and 61.80% encapsulation efficiency. Compared with the free anthocyanin solution, the anthocyanin-loaded chitosan nanoparticles showed a slowed degradation in simulated gastrointestinal fluid. Compared with the free anthocyanin solutions in a model beverage system, the stability of the anthocyanins was increased in the anthocyanin-loaded chitosan nanoparticles.